Case report: The power of immunotherapy in advanced cutaneous squamous cell carcinoma - Brockwell, Maximilian; Husain, Marium; Verschraegen, Claire; Wu, Richard; Tinoco, Gabriel (Frontiers in Oncology, 2023)
We describe the case of a neglected cutaneous squamous cell carcinoma with extensive facial involvement. The patient is a male in his late 70s who presented to dermatology with a large destructive facial mass that had increased in size gradually over 3 years and then rapidly proliferated, consuming a large portion of his left maxillofacial region. While the immediate reaction was referral to hospice care, medical oncology recommended treatment with cemiplimab, an immune checkpoint inhibitor. Collaboration with multiple providers facilitated the delivery of a multidisciplinary approach utilizing immunotherapy with QUAD shot radiotherapy. The immunotherapy treatment resulted in a dramatic disease regression, but the large facial anatomical defect caused by the carcinoma remained. The patient is undergoing reconstructive surgeries. This case illustrates the potential for significant response with immune checkpoint inhibitors delivered in combination with cyclical hypofractionated radiation therapy for patients with cutaneous squamous cell carcinoma, even in very advanced disease.